Testing neurophysiological markers related to fear-potentiated startle. (September 2018) - Seligowski, Antonia V.; Bondy, Erin; Singleton, Paris; Orcutt, Holly K.; Ressler, Kerry J.; Auerbach, Randy P.
Highlights: Examined differences in P100 and LPP amplitudes during a fear-potentiated startle paradigm. LPP amplitudes were significantly enhanced following the CS+ relative to CS-. The LPP difference wave (CS+ minus CS-) predicted FPS scores for the CS-. Abstract: Fear-potentiated startle (FPS) paradigms provide insight into fear learning mechanisms that contribute to impairment among individuals with posttraumatic stress symptoms (PTSS). Electrophysiology also has provided insight into these mechanisms through the examination of event-related potentials (ERPs) such as the P100 and LPP. It remains unclear, however, whether the P100 and LPP may be related to fear learning processes within the FPS paradigm. To this end, we tested differences in ERP amplitudes for conditioned stimuli associated (CS+) and not associated (CS-) with an aversive unconditioned stimulus (US) during fear acquisition. Participants included 54 female undergraduate students (mean age = 20.26). The FPS response was measured via electromyography of the orbicularis oculi muscle. EEG data were collected during the FPS paradigm. While the difference between CS+ and CS- P100 amplitude was not significant, LPP amplitudes were significantly enhanced following the CS+ relative to CS-. Furthermore, the LPP difference wave (CS+ minus CS-) was associated with FPS scores for the CS- during the later portion of fear acquisition. These findings suggest that conditioned stimuli may have altered emotional encoding (LPP) during the FPS paradigm. Thus, the LPP may be a promising neurophysiological marker that is related to fear learning processes.